The Importance of Covering National Identity Issues in Cultural and Educational Performances - Qayumova Dilorom Quvondiqovna (Zien Journals, 2022)
The worldview is a set of knowledge, imagination and ideas that are organized, transformed into a holistic conscious system, which encourages a person to occupy a worthy place in society while maintaining his identity. One of the main goals and tasks of the mass media is the coverage of national identity tables in New World Youth loyalty to the motherland, love of national values and traditions, kindness to their loved ones, loyalty to the chosen path - profession, profession and belief by means of cultural educational broadcasts broadcast on TV channels of our country. Thinking in a new way and thinking in a new way are the products of national consciousness, worldview and being brought up and polished in the spirit of the ideology of independence. In this article, views and comments will be made on the importance of covering the issues of national identity in cultural and educational performances.
Keywords: National Shows; Importance of mass media; shows; culture